Retrograde Stanford type A dissection caused by a multilayer stent graft in a patient with chronic type B dissection. (22nd November 2018) - Schafigh, Myriam Johanna; Kohistani, Zaki; Schiller, Wolfgang; Probst, Chris
Abstract: A patient with progressive chronic type B dissection and contraindication for open surgery underwent thoracic endovascular aortic repair using a Cardiatis Multilayer Flow Modulator ® . Two weeks after the intervention, the patient experienced a ruptured retrograde type A aortic dissection caused by the stent's uncovered proximal ends.